An Analysis and Design of Web-Based Learning GoProfTeach as Interactive Learning Tools. (October 2020) - Suryawati, E; Rahmi, F O; Rizki, M; Arnan, R H
Abstract: This study aims to analyze the need for:1) analyzing resources availability 2) analysing the TPACK (Technological, Pedagogical, and Content Knowledge) profile of preservice biology teachers 3) designing GoProfTeach as a web-based learning tool for in-service and pre-service teachers. In doing so, it followed ADDIE development model. The instrument for data collection was a validated TPACK test. This article, in particular, discusses the results of the study in the first year of the analysis and design phase. The instrument for data collection included documents checking sheets, questions validation sheets and a Technological Pedagogical Content Knowledge (TPACK) test. The results of resources availability analysis and TPACK tests indicate that there is a need for the development of web-based learning resources as a means of increasing the ability of TPACK of pre-service and high school Biology teachers. The contents that have been designed include; 4 sets of practice exercises, 4 modules, and 2 virtual lab topics. Following the research findings, the website contents will be further developed to make sure that they be used as an independent and interactive learning source for undergraduate students and pre-service Biology teachers who will take the Teacher Professional Education Program (PPG) and PPG Student Competency Test.